Implicit Motives as Determinants of Networking Behaviors - Wolff, Hans-Georg; Weikamp, Julia G.; Batinic, Bernad (Frontiers in Psychology, 2018)
In today’s world of work, networking behaviors are an important and viable strategy to enhance success in work and career domains. Concerning personality as an antecedent of networking behaviors, prior studies have exclusively relied on trait perspective that focus on how people feel, think, and act. Adopting a motivational perspective on personality, we enlarge this focus and argue that beyond traits predominantly tapping social content, motives shed further light on instrumental aspects of networking – or why people network. We use McClelland’s implicit motives framework of need for power, need for achievement, and need for affiliation to examine instrumental determinants of networking. Using a facet theoretical approach to networking behaviors, we predict differential relations of these three motives with facets of 1) internal vs. external networking and 2) building, maintaining, and using contacts. We conducted an online study, in which we temporally separate measures (N = 539 employed individuals) to examine our hypotheses. Using multivariate latent regression, we show that need for achievement is related to networking in general. In line with theoretical differences between networking facets, we find that need for affiliation is positively related to building contacts, whereas need for power is positively related to using internal contacts. In sum, this study shows that networking is not only driven by social factors (i.e., need for affiliation), but instead the achievement motive is the most important driver of networking behaviors.